PERANCANGAN BRAND IDENTITY XINXIN HOME INDUSTRY BERBASIS NATURE SEBAGAI UPAYA PENINGKATAN BRAND AWARENESS - Hidayat, Galih Rendy; Bahruddin, Muh; Riqqoh, Abdullah Khoir (Jurnal Art Nouveau, 2016)
The purpose of designing brand identity Xinxin is to increase efforts to promote the new company and brand awareness to the general public. The research was conducted using qualitative research method is to conduct interviews, observation, documentation, and literature to get the data used to support the drafting of designing brand identity. Data were analyzed using multiple stages, namely data reduction, data presentation, and conclusion. From the data analysis found some keywords that refer to branding communications strategy that will be used to reach the intended target audience. After analyzing the data, found a concept or keyword designing brand identity that is